ROLE OF MULTIDETECTOR COMPUTED TOMOGRAPHY SCAN IN THE ASSESSMENT OF MEDIASTINAL MASSES - RAI, HIMAL; DEBNATH, MANNA; P VERMA, ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were to determine the sensitivity and specificity of multidetector computed tomography (MDCT) in the evaluation of masses present in the mediastinum and to determine the localization and the common age group exposed to mediastinal masses. Methods: A retrospective cross-sectional study included 33 males and 21 females’ samples in the age range between 20 to 70 years. The patients who are specifically suspected of mediastinal masses were included in this research study and accumulated the data. The research was conducted between August 2017 to March 2018. The analysis of the data was performed using Microsoft Excel 2010. Results: Patients were referred for MDCT scan of the chest to the department of radiodiagnosis with a clinical suspicion of a mediastinal mass or who had an abnormal chest radiograph suggestive of mediastinal mass during the study period. The final result of the study clearly indicates that the majority of the patients that fall within the age group of 40–49 years and 50–59 years have the highest probability of occurring mediastinal masses. Conclusion: The present study concluded that anterior mediastinum is the most usual compartment involving the formation of mediastinal mass, followed by the posterior and middle compartment. MDCT is the modality of choice, which can evaluate mediastinal mass with higher accuracy.